Combining environmental niche models, multi-grain analyses, and species traits identifies pervasive effects of land use on butterfly biodiversity across Italy - Riva, Federico (Global change biology, 2023)
© 2023 The Authors. Global Change Biology published by John Wiley & Sons Ltd.